DETERMINAN KEJADIAN TUBERKULOSIS PARU PADA MASYARAKAT USIA PRODUKTIF DI INDONESIA (ANALISIS DATA RISKESDAS 2018) - Natasya Anggraeni Azis (2023)
Tuberculosis is a contagious disease that considered as a significant global health challenge. Indonesia is ranked as the second country with the highest TB burden worldwide (354 per 100.000 population), with the majority of cases occurring among the productive age population (15-64 years old). The number of TB cases remains significantly distant from the targets set by the National Medium-Term Development Plan (RPJMN) and the 2020-2024 National Health Development Strategy, which aim to reduce the incidence of tuberculosis to 190 per 100.000 population. The objective of this study is to identify the determinants of pulmonary tuberculosis in the productive age population in Indonesia. This is a cross-sectional study that utilized secondary data from the Indonesia Basic Health Research (Riskesdas) 2018. The Riskesdas 2018 population is all households in Indonesia. The research samples that were analyzed further in this study were respondents with complete data with a total of 166.887.905 people. The data were analyzed by using chi-square tests and logistic regression. Based on the final multivariate model, gender, age, education level, occupation, smoking behavior, diabetes mellitus, and house lighting exhibit a significant relationship with pulmonary tuberculosis cases among the productive age population. Diabetes mellitus emerges as the dominant risk factor in pulmonary tuberculosis (POR = 2.7, 95% CI: 2.068-3.477). Based on the research findings, stakeholders are encouraged to take immediate actions in addressing tuberculosis problem among the productive age population, particularly in individuals at higher risk of developing pulmonary tuberculosis. Integration of tuberculosis and diabetes mellitus screening and treatment is needed to improve disease monitoring and notification system.